Relationship between Renal Function Tests and the Levels of MDA, Zinc, and Cadmium among Painters in Sulaimani - A. Ahmed, Zheen (Iraqi Journal of Pharmaceutical Sciences, 2017)
Kidney damage in workers within environments of highly expected exposure to toxin, including heavy metals, could be a primary marker to expect hazards in population exposed to low levels of many environmental pollutants. The present study was designed to evaluate the possible effect of environmental exposure to cadmium and zinc on renal function among painters in Sulaimani city. Cross sectional study was performed on 37 male painting workers in Sulaimani city. Each worker was interviewed using structured questionnaire. Twenty five non-exposed healthy subjects were included as control group. Venous blood samples (10 ml) were obtained by vein puncture from both subjects and utilized for estimation of serum urea, creatinine levels, serum levels of cadmium (Cd) and zinc (Zn), and for the estimation of malondialdehyde. The results show that serum urea levels were significantly elevated in painters; meanwhile, no significant difference was reported in serum creatinine levels. The results indicated that both serum levels of (Cd) and (Zn) were not significantly elevated in painting workers; however, MDA levels were significantly elevated in painters compared to control group. In conclusion, the association of cadmium and zinc levels with the disturbance in renal function is not clear in painters working in Sulaimani city.Keywords: Painting workers, Cadmium, Zinc, renal function, oxidative stress